(untitled) (Research, Society and Development, 2021)
Recognized as a dimension that is associated with care, religiosity/spirituality (R/S) has been studied as a coping resource in health-disease processes. However, not much space has been offered in the curricula of health sciences courses. This study aims to describe how the dimension of R/S has been addressed in psychological interventions in the hospital context. This is a case report of care developed with a patient diagnosed with HIV/aids in a university hospital in the interior of the state of Minas Gerais, Brazil. In this case, we tried to demonstrate how R/S was experienced by the patient, problematizing the positive and negative aspects of this dimension in her life. The data presented make it possible to understand the ways in which R/S can be welcomed by psychologists in their listening, in line with the assumptions of comprehensive and humanized care in the context of public health. The importance of welcoming the R/S at the hospital and the need for greater preparation of professionals for this practice is reiterated.